(untitled) (Práxis Educativa, 2024)
This article aims to analyze Cesar Prieto Martinez’s actions in the educational reform in Paraná, Brazil, between 1920 and 1924, using the discussions in the newspaper Gazeta do Povo as the main source. The objective was to understand how the reform influenced the organization of the school system and teacher training. Methodologically, the research was based on a documentary analysis of the content of the newspaper editions and Martinez’s reports. The theoretical approaches of the research were based on interpretations by intellectuals such as Gramsci and positivism, treating education as a means of social control and modernization. As a result, the national character of the reform and the promotion of hygienism are highlighted, as well as the creation of a workforce for capital, which made the reform controversial and resistant. Keywords: Cesar Prieto Martinez. Gazeta do Povo. Educational reform.